Tackling burden in ART: an integrated approach for medical staff - Boivin, Jacky; Wischmann, Tewes (Human reproduction, 2012)
Abstract. Discontinuation is a problem in fertility clinics. Many couples discontinue assisted reproductive technologies (ART) without achieving a live birth f